2022
DOI: 10.7759/cureus.28379
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Applications of 3D Design and Printing in Dentistry Among Dental Practitioners in Saudi Arabia: A Questionnaire-Based Survey

Abstract: Background : This knowledge, attitude, and practices (KAP) survey will provide baseline data and identify gaps that may facilitate understanding and further action to plan, implement, and evaluate practice toward 3D-printing technology among dental practitioners in Saudi Arabia. Aims and objectives: The present study aims to assess dental practitioners' self-reported knowledge, attitude, and practice of 3D printing in Saudi Arabia. Methodology: A cross-sectional, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
(39 reference statements)
1
3
1
Order By: Relevance
“…The majority of the participants in our study needed to become more familiar with techniques used for 3D printing, such as SLS 84(59.6%), FDM 102(72.3%) and DLP 106(75.2%). In contrast to our study Dhokar et al; reported that 85.2% of the respondents were aware of this technology 18 . Most of the respondents in the current survey responded that they use 3D printing to fabricatetemporary crowns 30(21.3%) 3Dmodels 22(15.6).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The majority of the participants in our study needed to become more familiar with techniques used for 3D printing, such as SLS 84(59.6%), FDM 102(72.3%) and DLP 106(75.2%). In contrast to our study Dhokar et al; reported that 85.2% of the respondents were aware of this technology 18 . Most of the respondents in the current survey responded that they use 3D printing to fabricatetemporary crowns 30(21.3%) 3Dmodels 22(15.6).…”
Section: Resultscontrasting
confidence: 99%
“…Dhokar et al assessed the practices of 3D technology and reported that 43.4% were using this technology for surgical guide preparation, 78.7% were using 3-D models,and 31.3% were designing customized prostheses. PEEK and 54(38.3%)PMMA 63(44.7%) were the most commonly used polymers, similar to our study results 18 . Pillai et al also reported that PMMA and PEEK are the most widely used polymers.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A previous Saudi study with the same objective reported that, 98% of people were found to be aware that 3D printing is used in Saudi Arabian dentistry, whereas 2% were not. The placement of implants was deemed to be the most correct and least complicated treatment by 78.60% of dentists and the least accurate and most complicated procedure by 21.40% of dentists (Suganna et al, 2022). Orthodontists in India were evaluated for their 3D printing knowledge, attitudes and practices in a study by claimed that 47.5% of orthodontists had used this technique; however, the current study only found that 38.7% of dental practitioners had some familiarity with it, which may be because all graduates and postgraduates were included.…”
Section: Discussionmentioning
confidence: 99%
“…The research proposal was approved by the Regional Research and Ethics committee of King Abdulaziz University, Jeddah, with letter number (129- [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%